Spirituality and lifestyle in Human Medicine students of Universidad Peruana Unión, Lima 2017 - Alva Rosnay, Lea Rosmery (2018)
Objective: To determine the relationship between spirituality and lifestyle in students of Human Medicine. Materials and methods: Quantitative approach, non-experimental design, correlation type and cross-sectional type. The selection of the sample was made by non-probabilistic sampling for convenience and was made up of 176 students. The questionnaire used for data collection was the “spirituality questionnaire” created by Parsian and Dunning (2009) and translated and adapted into Spanish by Diaz (2012). In turn, to measure the lifestyle variable, it was used the “SN - 52” questionnaire, created by Walker, Sechrist, and Pender (1996). It should be noted that both instruments presented a high Cronbach Alpha coefficient with a value of 0.9, demonstrating their reliability. Results: There was a relationship between spirituality and the lifestyle with a p-value of 0.002, according to the Chi-square statistical test. Similarly, a relationship was found between the dimensions of spirituality and lifestyle with a p-value <0.05. Conclusion: There is a relationship between the study variables.